Biologically synthesized silver nanoparticle-based colorimetric sensor for the selective detection of Zn2+. Issue 111 (26th October 2015) - Ihsan, Muhammad; Niaz, Abdul; Rahim, Abdur; Zaman, Muhammad Iqbal; Arain, Muhammad Balal; Sirajuddin; Sharif, Tehmina; Najeeb, Memoona
Abstract : Schematic illustration for the colorimetric detection of Zn 2+ . Abstract : A simple, selective and cost effective colorimetric sensor has been investigated for the detection of Zn 2+ using biologically synthesized silver nanoparticles (AgNPs). The AgNPs were prepared from the leaf extract of Amomum subulatum via two different procedures i.e., at room temperature and by a heat treatment procedure. The AgNPs prepared through the heat treatment procedure exhibited efficient results. The as synthesized AgNPs were studied by simple UV-vis spectroscopy which showed an intense absorption band at 425 nm which was further confirmed by FT-IR and SEM analysis. The synthesized AgNPs exhibited a good colorimetric sensing property towards Zn 2+ by changing the color of the solution from yellowish-brown to colorless accompanying a decrease in absorption intensity. The proposed detection mechanism of the sensor has been discussed. The sensor showed an excellent linear response towards Zn 2+ in the concentration range from 1 × 10 −5 to 8 × 10 −5 M with a correlation coefficient ( R 2 ) of 0.996. The detection limit of the method was found to be 3.5 × 10 −6 M. There was no interference effect observed for Zn 2+ detection in the presence of other heavy metal ions. The proposed sensor was successfully applied for the detection of Zn 2+ in drinking water samples.